The design and methodology of a usability protocol for the management of medications by families for aging older adults - Quintana, Y.; Fahy, D.; Abdelfattah, A. M.; Henao, J.; Safran, C. (BMC medical informatics and decision making, 2019)
Health research apps often do not focus on usability as a design priority. This is problematic when the population of interest is disproportionately underrepresented as users of mobile apps, especially observed with aging older adults (> = 75). Challenges with the adoption of health information technology (HIT) among this group are exacerbated by poor design and user interface/experience (UI/UX) choices. This protocol describes the testing and evaluation process of one HIT app for the family-based collaboration platform InfoSAGE. We aim to recruit twenty subjects from both informal family-caregivers and aging older adults to examine the usability of the InfoSAGE mobile medication manager. Participants will be audio and visually recorded, in addition to the use of screen capture recordings, while 'thinking aloud' as they complete eight common use-case scenarios. Multiple independent reviewers will code video and audio recordings for thematic analysis and use problems will be evaluated. Success and failure of each scenario will be determined by completion of sub-events. Time-to-complete analysis will be used to ascertain the learning curve associated with the app. Frequently observed problem areas will be used as the basis of further evolution of the app, and will further inform generalized recommendations for the design of HIT apps for research and public use. This study aims to improve the model of development for dual user populations with dissimilar technological literacy to improve retention and use. Results of this study will form the foundation of a design framework for mobile health apps.